2006
DOI: 10.1590/s0101-20612006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo do efeito da irradiação gamma (60CO) na qualidade da cachaça e no tonel de envelhecimento

Abstract: RESUMOO processo de envelhecimento ou maturação das bebidas proporciona uma melhora nas características sensoriais da cachaça, tornandoa de qualidade superior e de maior valor econômico. O método tradicional de maturação de bebidas é sua interação com madeiras, sendo que a irradiação pode acelerar este processo de envelhecimento. A cachaça e os tonéis de carvalho de 20 L de capacidade foram submetidos à irradiação gama (150 Gy). Análises físico-químicas e cromatográficas foram realizadas periodicamente ao long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
11

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 12 publications
0
19
0
11
Order By: Relevance
“…It were shown that gamma radiation can increases (Moussaid et al, 2000, Mechi et al 2005, Miranda et al 2006, Bhat et al 2007, Stajner et al 2007, decreases (Villavicencio et al 2000;Brigide & Canniatti-Brazaca, 2006, Toledo et al, 2007 or unchanged levels of total phenols and/or tannins (Koseki et al, 2002) in plant extracts from some plants, and raw or cooked, which had considerable percentage of moisture, favoring the indirect effects of radiation (Mechi et al, 2005, Brigid & Canniatti-Brazaca, 2006. These studies are unprecedented as the characterization of dry vegetable matter, which dominates the interaction of gamma radiation from the direct effect.…”
Section: Resultsmentioning
confidence: 99%
“…It were shown that gamma radiation can increases (Moussaid et al, 2000, Mechi et al 2005, Miranda et al 2006, Bhat et al 2007, Stajner et al 2007, decreases (Villavicencio et al 2000;Brigide & Canniatti-Brazaca, 2006, Toledo et al, 2007 or unchanged levels of total phenols and/or tannins (Koseki et al, 2002) in plant extracts from some plants, and raw or cooked, which had considerable percentage of moisture, favoring the indirect effects of radiation (Mechi et al, 2005, Brigid & Canniatti-Brazaca, 2006. These studies are unprecedented as the characterization of dry vegetable matter, which dominates the interaction of gamma radiation from the direct effect.…”
Section: Resultsmentioning
confidence: 99%
“…According to Egorov and Rodopulo (1994), mentioned by Miranda, Hoii and Alcarde (2006), furfural concentration, a compound that can originate from the degradation of the wood pentose, tends to increase with the maturation of the distillate, which can explain the high values found for this compound before the filtering. In the present study, it was verified that the filtering process was efficient in the removal of this compound reducing it to levels below those established by the legislation.…”
Section: Physicochemicalmentioning
confidence: 97%
“…The transformation from the originally strong product into a product with softer and desirable characteristics also occurs, increasing its acceptability by the consumer FARIA, 2000). Miranda, Hoii and Alcarde (2006) state that in such process, several chemical reactions that provide the incorporation of compounds originating from the wood of the containers occur, as well as reactions among some compounds present in the drink originating from pre-aging stages.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The differences can be explained due to factors such as type of wood used in the aging, barrel ability, storage time of the beverage, size and pre-treatment of barrel, environmental conditions as temperature and humidity of storage environment and alcohol content of the beverage. These related parameters influence the composition of phenolic compounds extracted from wood during the aging process of the beverage [7].…”
Section: Quantification Of Phenolic Compoundsmentioning
confidence: 99%